Fla. Act of Aug. 8, 1868, as codified in Fla. Rev. Stat., tit. 2, pt. 5 (1892), at 2425 - (:unkn) unknown (General Publisher, 1868)
Prohibited the manufacture or sale of slungshots or metallic knuckles. Punishable by imprisonment for up to 6 months or a fine up to $100.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS